DIVERGENT FINANCIAL PERFORMANCE UNDER PUBLIC HOSPITAL AUTONOMY: COMPARATIVE EVIDENCE FROM VIETNAM’S TERTIARY CARE SECTOR (Vietnam Journal of Community Medicine, 2026)
Objective:  This study explores how hospital type mediates financial performance within a shared financial autonomy framework, highlighting organizational and structural factors that influence financial outcomes under quasi-market conditions.Methods:  A comparative institutional case study was conducted at two tertiary public hospitals in Ho Chi Minh City from 2022 to 2024: a general hospital and a specialized pediatric hospital. Using a mixed-methods approach, audited financial statements were analyzed to examine trends in revenue, expenditure, operating surplus, and revenue composition. Qualitative data were collected through semi-structured interviews with hospital managers and analyzed thematically.Results:  Both hospitals reported substantial revenue growth exceeding 50% over the study period. However, their financial trajectories diverged markedly. The general hospital demonstrated stable revenue–expenditure alignment and a diversified income structure. In contrast, the specialized hospital exhibited narrowing margins driven by cost escalation and heavy dependence on social health insurance reimbursements. Qualitative findings suggested that expenditure rigidity and purchaser dominance constrained managerial autonomy, particularly in the specialized setting.Conclusion: Hospital financial autonomy does not generate uniform outcomes. Revenue concentration and cost rigidity may produce divergent financial trajectories even under a shared policy framework. Financial autonomy models should therefore be adapted according to hospital type and financing structure.
Keywords: Hospital financial autonomy; Public hospitals; Revenue concentration; Cost rigidity; Social health insurance; Vietnam.